Investigation and analysis of standardized training for residents of general practitioners of Gansu Province in China - Hongjing Wang; Jin He; Dongzhi Zhang; Yue Wu; Peidong Wang; Hui Cai (BMC Family Practice, 2020)
Abstract Background China’s standardized training for residents of General Practitioners (GPs) is aimed at providing the postgraduate training for family doctors who will serve the primary health care institutions. The aim of this paper is to investigate the standardized training situation, satisfaction with standardized training, work situation, intention, satisfaction and attitude of GPs who have finished standardized training. Methods This study was undertaken in 6 training hospitals in Gansu province using a questionnaire with 45 questions. Results Approximately 275 residents of GPs were enrolled. Finally, 263 residents completed the questionnaire (95.64% response rate), including 133 females (50.57%) and 130 males (49.43%) with an average age of 28 years (standard deviation, 1.93 years; range, 25–36 years). Additionally, 56.65% were single and 43.35% were married. Of all subjects, 92.40% residents had obtained certification of standardized training for residents of GPs and only 39.54% residents were satisfied with monthly income during training. There were 171 oriented rural medical graduates, of whom, only 42.69% expressed the willing to continue working in the primary health care institutions after the serve time (6 years) expired. Around 86.31% of residents of GPs who had finished standardized training got jobs with more than half serving in the primary health care institutions. For medical institutions and sanitary bureau were clear about general medicine policies, only 29.96% subjects registered as GPs. Among the residents in general practice department, 68.42% were engaged in the diagnosis and treatment of common disease and frequently-occurring diseases as well as referral of patients. The percentage of residents who were satisfied with the job and income were 30.40 and 14.98%, respectively. Conclusion Standardized training for residents of GPs in China is gradually improving. In order to cultivate more GPs and increase their willing to serve in the primary health care institutions, it is necessary to formulate and execute better policy of GPs, publize general medicine and improve the training quality.